Perencanaan Fasilitas Perlengkapan Jalan Terhadap Geometrik Jalan (Studi Kasus : Desa Jake Kabupaten Kuantan Sengingi) - Dilla Kartika; Sri Djuniati; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Jake Village road is a road that located in Kuantan Sengingi Regency, Riau Province. This road categorized as primary collector roads one of alternative road connected from Pekanbaru to Jambi via Lubuk Ambacang. The existing traffic from Jake Village road is dominated by truck vehicle as the road passes through the rubber and oil palm plantation area. The condition of road equipment facilities on Jake village road is still minimal, so an analysis of the placement of road equipment facilities are needed based on the Department of Transportation regulations 2006 and the geometric regulations of the Bina Marga Road in 1997. The results of the analysis on the Jake Village Road required 75% of warning signs and 99% of solid markers, because there are many sharp bends, climbs and derivatives along this road.Keywords : Jake Village, road geometric, Signs and Mark